Government Spending, Rights, and Civil Liberties. (IMF Working Papers; Working Paper, 2000)
Government spending plays a critical role in protecting and enforcing rights and civil liberties. Empirical evidence for a sample of industrial and developing countries shows that government expenditures on defense, law and order, social security, education, and health care are associated with three rights indicators-property rights, equality of citizens before the law, and economic freedom. In particular, an increase in spending on law and order seems to improve the indicators of rights and civil liberties, and lower budget deficits seem to improve property rights and equality before the law. Of great importance is the finding that corruption is associated with worse rights indicators.